Vezérfonál a magyar tragédiák korának (1944 –1948) szintéziséhez 1: : a magyar-csehszlovák lakosságcsere - Gulyás, László (Közép-Európai Közlemények, 2024)
During the age of Hungarian tragedies (March 19, 1944–June 14, 1948) seven tragedies befell the Hungarian state and Hungarian nation. One of these is the Czechoslovak-Hungarian population exchange. In our study, we review the history of this.